AMELOGLYPHICS - A REVIEW - S, Amrithaashri; Santhanam, Archana (International Journal of Psychosocial Rehabilitation, 2020)
Soft tissues are unable to provide reliable information for human identification in mass disasters; it is largely feasible with skeletal remains, especially teeth. There is a crucial need for new and dependable methods for recognition and confirmation of victims in mass disasters. Forensic odontology employs various methods like rugoscopy, dental labeling, DNA analysis from dental pulp, bite mark analysis, etc. Currently it embraces the study of enamel rod end patterns. Ameloglyphics is an analysis of the end patterns of the enamel rod. These patterns have been found to be unique to the individual teeth of the same individual, as well as to different individuals. A potential association between the type of enamel rod end pattern and the incidence of dental caries can help to predict the individual’s susceptibility to caries and to implement preventive measures. Individual identification is becoming more important than ever in today’s world. Numerous techniques have been used for victim recognition in forensic dentistry, including ruboscopy, cheiloscopy, bite marks, dental impressions (ameloglyphics), radiographs, photographic samples, and biochemical approaches. The use of enamel rod end patterns may be used to identify the susceptibility of an individual to common dental conditions that are acquired during one’s lifetime.